Sex Differences in 1-Year Rehospitalization for Heart Failure and Myocardial Infarction After Primary Percutaneous Coronary Intervention - Zheng, Huili (EXCERPTA MEDICA INC-ELSEVIER SCIENCE INC, 2021)
AMERICAN JOURNAL OF CARDIOLOGY